Progressive systemic sclerosis and acute interstitial lung disease in children: a case report - Núñez Moscoso, Luis Enrique (2025)
Childhood or juvenile scleroderma is the third most common pediatric chronic rheumatic diseasefollowing juvenile idiopathic arthritis (JIA) and systemic lupus erythematosus (SLE). It has twomain forms: systemic and localized. The available information remains very limited, as few serieshave been published, and most of them include a small number of patients. On the other hand,the classification and management of the disease have evolved over time.The diagnosis of interstitial lung diseases (ILDs) in adults—and even more so in children—constitutes a significant challenge for clinicians. ILDs of inflammatory origin are rare in adultsand can be considered almost exceptional in children; the largest series report no more than 50cases. Autoimmune forms of IDLs in children represent a particularly complex category, as theyinvolve aberrant immunological mechanisms that affect both the lungs and other organs. This cancomplicate diagnosis and treatment, and may worsen the prognosis.The relationship between systemic sclerosis in children and acute ILD is complex and remainsunder investigation. Early diagnosis, clinical assessment and appropriate treatment are essentialto improve the prognosis and quality of life of affected pediatric patients. Given the particularrelevance of both diseases and the limited information available in the literature, we present thecase of a 6-year-old patient in whom both occurred at different stages of disease.